1976
DOI: 10.1111/j.1365-2265.1976.tb02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone Release‐inhibiting Hormone and Bromocryptine (Cb 154) in States of Abnormal Pituitary‐adrenal Function

Abstract: Growth hormone release-inhibiting hormone (GHR-IH) was administered to five patients with abnormal pituitary-adrenal function. There was immediate suppression by about 50% of ACTH levels in two patients who had undergone bilateral adrenalectomy because of Cushing's disease; one of them had Nelson's syndrome. Bromocryptine (2-5 mg) suppressed ACTH levels by 62-67% for more than 6 h in these patients. GHR-IH did not significantly influence cortisol secretion by an adrenal carcinoma and only slight changes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…Thus, it may be plausible to ascribe the effect of bromocriptine, a specific dopamine receptor agonist with a prolonged action, to a direct inhibition of ACTH release from corticotroph adenoma cells in these patients. Compared with the previous reports on the efficacy of bromocriptine in patients with Cushing's disease (9)(10)(11)(12)(13)(14)(15), the percentage of responders in the present study ( (1 ,uM) (Fig. 7).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Thus, it may be plausible to ascribe the effect of bromocriptine, a specific dopamine receptor agonist with a prolonged action, to a direct inhibition of ACTH release from corticotroph adenoma cells in these patients. Compared with the previous reports on the efficacy of bromocriptine in patients with Cushing's disease (9)(10)(11)(12)(13)(14)(15), the percentage of responders in the present study ( (1 ,uM) (Fig. 7).…”
Section: Resultsmentioning
confidence: 57%
“…Subsequent studies confirmed the efficacy of this drug in the management of some, though not all, patients with Cushing's disease and Nelson's syndrome (2)(3)(4)(5)(6)(7)(8). Bromocriptine, a dopaminergic agonist, likewise has been shown to lower plasma ACTH levels in some patients, and its clinical use is currently being evaluated (9)(10)(11)(12)(13)(14)(15). These works opened the possibility of medical management of the disorder.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been reported that the increased secretion of ACTH from the pituitary is able to be inhibited by the administration of SRIF or its long-acting analogue in Nelson's syndrome (Tyrrell et al, 1975, Benker et al, 1976, Lamberts et al, 1989, Reichlin, 1983. However, it was uncertain whether SRIF inhibits secretion of CRH or not.…”
Section: Discussionmentioning
confidence: 99%
“…(SRIF) or long-acting SRIF analogue has been reported to be effective in suppressing the secretion of pituitary hormones, such as growth hormone (GH) in patients with acromegaly (Yen et al, 1974, Plewe et al, 1984, Kelijman et al, 1988, thyrotropin (TSH) in patients with TSH-secreting pituitary tumors (Comi et al, 1987, WemeauTet al, 1988 and corticotropin (ACTH) in patients with Nelson's syndrome (Tyrell et al, 1975, Benker et al, 1976, Lamberts et al, 1989 or with ectopic ACTH secretion (Bertagna et al, 1989). However, it is not certain whether the agent is effective in inhibiting the release of hypothalamic releasing factors, such as GH-releasing hormone (GH-RH), TSH-releasing hormone (TRH) and ACTHreleasing hormone (CRH) (Lamberts, 1988).…”
Section: Somatostatinmentioning
confidence: 99%